The Anti-Nociceptive Effects of Nicotine in Humans: A Systematic Review and Meta-Analysis - Yujia Luo; Yating Yang; Carl Schneider; Thomas Balle (MDPI AG, 2023)
Background: Pain can have a serious impact on a patient's physical, mental, and social health, often causing their quality of life to decline. Various nicotine dosage forms, such as nicotine patches and nasal spray, have been developed and used as analgesics in clinical settings. However, there is controversy over the anti-nociceptive effects of nicotine among different clinical trials. The purpose of this meta-analysis is to quantify the analgesic effect of nicotine patches, nicotine nasal spray, and tobacco smoking on pain in humans. Methods: Relevant articles published in English prior to July 2023 were identified using the PubMed, Cochrane Library, and Embase online databases in accordance with PRISMA (2020) guidelines. Two reviewers independently screened and selected studies, extracted data, and assessed the quality of the included studies using version 2 of the Cochrane risk-of-bias tool for randomized trials (RoB 2). RStudio was used for data synthesis, heterogeneity assessment, sensitivity analysis, publication bias assessment, trim-and-fill analyses, and generating forest plots. Results: Sixteen eligible articles, including k = 5 studies of pain tolerance (n = 210), k = 5 studies of pain threshold (n = 210), and k = 12 studies of pain scores (N = 1249), were included for meta-analysis. Meta-analytic integration for pain threshold (Hedges' g = 0.28, 95% CI = 0-0.55, Z = 1.99, p = 0.05) and pain tolerance (Hedges' g = 0.32, 95% CI = 0.05-0.59, Z = 2.30, p = 0.02) revealed that nicotine administered via tobacco smoke generated acute analgesic effects to thermal stimuli. Meta-analytic integration for pain scores revealed that nicotine had a weak anti-nociceptive effect on postoperative pain of −0.37 (95% CI = −0.77 to 0.03, Z = −1.80) but with no statistical significance (p = 0.07). In addition, a limited number of included studies revealed that long-term smoking produced hyperalgesia that may be characterized as small to medium in magnitude (Hedges' g = 0.37, 95% CI = 0.29-0.64, Z = 5.33, p < 0.01). Conclusion: These results help to clarify the mixed outcomes of trials and may ultimately inform the treatment of pain. We observed that acute nicotine administration prolonged the laboratory-induced pain threshold and tolerance time and may mildly relieve postoperative pain. In addition, long-term tobacco smoking may have a nociceptive effect on different types of chronic pain. More research is needed to determine the anti-nociceptive effects of nicotine in humans, and to understand the optimal timing, dose, and method of delivery of nicotine.